2020
DOI: 10.1371/journal.pmed.1003288
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of height and risk of atrial fibrillation: A Mendelian randomization study

Abstract: Background Observational studies have identified height as a strong risk factor for atrial fibrillation, but this finding may be limited by residual confounding. We aimed to examine genetic variation in height within the Mendelian randomization (MR) framework to determine whether height has a causal effect on risk of atrial fibrillation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 43 publications
3
43
0
1
Order By: Relevance
“…39 Whilst the reason underpinning these changes is unclear, a recent Mendelian randomization study suggested taller people had higher risk of atrial fibrillation and hence failure to take into account height in the analyses may have led to the positive observed association in the main analyses given some of the lung function instruments were also related to height. 40 This may also explain the null findings upon adjustment for height in the multivariable Mendelian randomization.…”
Section: Discussionmentioning
confidence: 97%
“…39 Whilst the reason underpinning these changes is unclear, a recent Mendelian randomization study suggested taller people had higher risk of atrial fibrillation and hence failure to take into account height in the analyses may have led to the positive observed association in the main analyses given some of the lung function instruments were also related to height. 40 This may also explain the null findings upon adjustment for height in the multivariable Mendelian randomization.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, consistent results were obtained in the recurring MR analyses. Another MR study ( 44 ) found that taller people had higher risk of AF and considering part instruments of the lung function were also related to height, which may account for the invalid results of height adjustment in GWAS summary data. Furthermore, the positive relation of FEV1/FVC with AF in our uvMR Egger analysis is somewhat unexpected although the association disappeared after adjusting for FEV1 and FVC in mvMR method.…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms that reached genome-wide significance ( p < 5 * 10 −8 ) were selected as instrumental variables. These SNPs were further linkage disequilibrium (LD)-pruned (distance threshold = 10,000 kb, r 2 < 0.001) to ensure independence among the genetic variants ( 28 ). If the selected SNPs were not collected in the GWAS of HF, proxy SNPs in the linkage disequilibrium ( r 2 > 0.8) were chosen for substitution.…”
Section: Methodsmentioning
confidence: 99%